PENEGAKAN HUKUM TERHADAP TINDAK PIDANAPENGANIAYAAN DI KABUPATEN KUANTAN SINGINGI DALAM PERSPEKTIF HUKUM PIDANA DAN HUKUM ADAT (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Criminal acts of "violence" whether committed by individuals or carried out together or in groups that can disturb public order can even disturb society. It seems that awareness to respect one's human rights and love for fellow human beings is diminishing or their growth is not as expected so that the behavior of "doing good" for others and others is increasingly invisible. The formation of crimes against the human body is referred to the protection of the legal interests of the body from actions in the form of attacks on the body or parts of the body that cause pain or injury, even because such injuries to the body can cause death. The torture is regulated in article 351 of the Criminal Code. In the Criminal Code this is called "persecution" but the Criminal Code itself does not contain the meaning of the persecution. Persecution in the Big Indonesian Dictionary contains meaning of arbitrary treatment. The definition of persecution contained in the Big Indonesian Dictionary is the meaning of broad meaning, including those involving feelings or the mind. Persecution referred to in criminal law is related to the human body. criminal fines imposed on perpetrators of criminal acts of persecution in the customary criminal law are intended to restore the (magical) balance that is disturbed by acts contrary to customary law.This type of research can be classified into sociological juridical research where the research tests the effectiveness of the current law. This sociological legal research is a type of research that is viewed from the purpose of legal research. Sociological or empirical legal research consists of legal identification (unwritten) and research on the effectiveness of the law. From the results of the study there are 2 main problems that can be concluded. First, the factors that cause the crime of maltreatment committed by adolescents in Kuantan Singingi Regency are due to sexual misconduct that occurs among adolescents as well as the lack of supervision conducted by parents to their children.Keywords: Abuse - Violence - Criminal Acts - Customary Law.